2015
DOI: 10.1016/j.cpc.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

GPU accelerated solver for nonlinear reaction–diffusion systems. Application to the electrophysiology problem

Abstract: Solving the electric activity of the heart posses a big challenge, not only because of the structural complexities inherent to the heart tissue, but also because of the complex electric behaviour of the cardiac cells. The multiscale nature of the electrophysiology problem makes difficult its numerical solution, requiring temporal and spatial resolutions of 0.1 ms and 0.2 mm respectively for accurate simulations, leading to models with millions degrees of freedom that need to be solved for thousand time steps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…From the computational point of view, a deeper investigation of the CV in the circumferential direction using a more realistic gastric geometry should be accomplished, considering also the presence of the fundus, which is electrically quiescent but responsible for other, specific mechanical effects, namely the storage function of the stomach. Also, more efficient numerical schemes and GPU‐based codes are foreseen to speed‐up the wide numerical analyses necessary to fully characterize a complex organ like the stomach.…”
Section: Resultsmentioning
confidence: 99%
“…From the computational point of view, a deeper investigation of the CV in the circumferential direction using a more realistic gastric geometry should be accomplished, considering also the presence of the fundus, which is electrically quiescent but responsible for other, specific mechanical effects, namely the storage function of the stomach. Also, more efficient numerical schemes and GPU‐based codes are foreseen to speed‐up the wide numerical analyses necessary to fully characterize a complex organ like the stomach.…”
Section: Resultsmentioning
confidence: 99%
“…With a computation time for the prediction best expressed in seconds, we have demonstrated that the time required to obtain a steady state of the cell models can be reduced by at least two‐thirds and possibly even more than 90 % , thus further enabling the use of personalized EP simulations in the clinic, as well as studies on larger populations than previously have been used. One should also note that this approach was used in combination with parallelization of the simulations, and there should be no obstacle per se to prevent combination of our technique with GPU‐based acceleration such as those presented by Rocha et al and Mena et al…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Cardiac electrical dynamics simulations is no exception to this trend. They evaluated not only the performance of adapted CPU implementations for GPUs, [33][34][35] but also different parallel strategies 11,20,[36][37][38][39] and numerical methods. They evaluated not only the performance of adapted CPU implementations for GPUs, [33][34][35] but also different parallel strategies 11,20,[36][37][38][39] and numerical methods.…”
Section: Related Workmentioning
confidence: 99%
“…[30][31][32] Several authors have tested GPU performance previously for different cardiac tissue models. They evaluated not only the performance of adapted CPU implementations for GPUs, [33][34][35] but also different parallel strategies 11,20,[36][37][38][39] and numerical methods. 40,41 Some authors have addressed the problem of implementing a solution for a PDE like Equation (3)…”
Section: Related Workmentioning
confidence: 99%